2015
DOI: 10.1108/cb-10-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Comparing usage between a Dynamic and a Static e-monograph Collection

Abstract: 2015),"Optimizing KBART guidelines to restore perpetual access", Collection Building, Vol. 34 Iss 1 pp. 13-16 http:// dx. Access to this document was granted through an Emerald subscription provided by emerald-srm:448207 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In his 2015 study, on e-monograph collection size and usage, Lamothe discovered a very similar relationship. He reported a very strong linear relationship between the number of e-monographs in a dynamic collection and their corresponding number of viewings (R 2 ϭ 0.91) (Lamothe, 2015). In this study, e-reference collection size and usage demonstrated an equally strong relationship R 2 ϭ 0.99 ( Figure 6).…”
Section: Analysis Of Dynamic and Static Collection Usagesupporting
confidence: 50%
See 3 more Smart Citations
“…In his 2015 study, on e-monograph collection size and usage, Lamothe discovered a very similar relationship. He reported a very strong linear relationship between the number of e-monographs in a dynamic collection and their corresponding number of viewings (R 2 ϭ 0.91) (Lamothe, 2015). In this study, e-reference collection size and usage demonstrated an equally strong relationship R 2 ϭ 0.99 ( Figure 6).…”
Section: Analysis Of Dynamic and Static Collection Usagesupporting
confidence: 50%
“…Dynamic e-monograph collections not only experienced greater level of usage than static collections but their usage continued to increase annually (Lamothe, 2015). Static e-monograph collections even recorded decreased levels of usage over time (Lamothe, 2015). That study, however, did not address e-reference usage.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations